Randomized, Placebo-Controlled, Double-Blind and Open-Label Studies in the Treatment and Prevention of Acute Diarrhea With Enterococcus faecium SF68 - Greuter, Thomas; Michel, Martin C.; Thomann, Daniela; Weigmann, Harald; Vavricka, Stephan R. (Frontiers in Medicine, 2020)
Enterococcus faecium SF68® (SF68) is a licensed pharmaceutical for treatment and prevention of diarrhea in Austria, Italy and Switzerland. However, as for other probiotics, evidence for its efficacy is based on small to medium-sized studies. Four unpublished studies on the treatment of acute diarrhea and the prevention of antibiotic-associated diarrhea were analyzed: one randomized, double blind, placebo-controlled trial (RCT) for treatment (n = 1,143), one open-label study for treatment (n = 5,093), one RCT for prevention (n = 1,397) and one open-label study for prevention (n = 4,340). Patients in the treatment-arm and the open-label studies received SF68 (b.i.d. for the prevention studies, t.i.d. for the treatment trials) for 7 days. Primary end points were time to resolution of diarrhea (treatment) and percentage of development of diarrhea (prevention). The primary endpoint of the treatment study was met with a decreased time to resolution of diarrhea in SF68-treated patients compared to controls (median 3 vs. 4 days, p < 0.001). Time to resolution of secondary symptoms was also significantly reduced. Preventive treatment with SF68 was more effective than placebo with development of diarrhea in 8.6 vs. 16.2% (p < 0.001). Results from the open-label studies were consistent with the RCTs. The incidence of adverse events were low (1.1 and 1.4% in the RCT and 4.7 and 7.4% in the open-label studies). SF68 is effective and safe in the treatment of acute diarrhea and prevention of antibiotic-associated diarrhea.